2019
DOI: 10.9744/ijbs.2.1.66-74
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IT Application to Organizational Performance mediated by warehouse management and customer relationship management

Abstract: In this thesis discuss the effect of Information Technology Application to Organizational Performance through Warehouse Management and Customer Relationship Management on company. In this study using primary data with a population of 109 companies and 52 samples of companies using data collection methods, namely 5 points Likert scale in the form of questionnaires distributed in companies that are groups on third-party logistics companies in Surabaya and Sidoarjo. This study uses Structural Equation Modeling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Moreover, the hypothesis (H8) test result showed a significant impact of green production on green distribution. This study supports the previous research stating that green production support green distribution [11,40,48]. However, green production should not stand alone in practicing the green concept.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the hypothesis (H8) test result showed a significant impact of green production on green distribution. This study supports the previous research stating that green production support green distribution [11,40,48]. However, green production should not stand alone in practicing the green concept.…”
Section: Discussionsupporting
confidence: 90%
“…Implementing information communication and technology (ICT) such as ERP can improve organizational performance in terms of reduced cost, improved quality, faster delivery, more product variety, and time to introduce new products to the market from other competitors [35]. A survey of 57 manufacturing companies in East Java, Indonesia, showed that information technology application affects organizational performance significantly [48]. Furthermore, previous research has also stated that companies that efficiently use the sources of information presented by ERP can improve the company's operational performance in areas such as process standardization and timely delivery of goods [14].…”
Section: Enterprise Resource Planning (Erp) Adoption and Operational ...mentioning
confidence: 99%
“…Supplier relationship management, one of the supply chain integration, significantly affects firm performance in the 3-star Hotels in Surabaya, Indonesia (Chandra Tanuwijaya et al, 2021). In addition, research on fifty-three 3PL logistics companies in East Java, Indonesia, indicated that customer relationship management, which is part of supply chain integration, significantly affects organizational performance (Santoso & Siagian, 2019). Furthermore, exchanging information about products, processes, schedules, and capabilities helps the network plant develop its production plan and produce goods on time (Cheng et al, 2016).…”
Section: Effect Of Supply Chain Integration On Operational Performancementioning
confidence: 99%
“…Information Technology (IT) Capability is the ability to obtain, fuse, and apply information technology resources to fulfill business needs and take advantage of business opportunities Smyrnios, 2019: Santoso andSiagian, 2019). It enables MSMEs to gather customer information at a low cost, which will increase marketing effectiveness and the ability to perform market segmentation and product differentiation.…”
Section: It Capabilitiesmentioning
confidence: 99%
“…On the contrary, without agility, companies only have a small chance to achieve superior performance (Chen et al, 2014). Information technology gives influence to the companies through a complementary relationship with assets and other companies' capabilities, and agility is an important mediator to see the influence of IT capabilities on a company's performance (Liu, Ke, Wei, & Hua, 2013;Santoso and Siagian, 2019;Jiputra et al, 2020). H4 : Organizational agility mediates the influence of IT capabilities on competitive advantage.…”
Section: It Capabilities Organizational Agility and Competitive Advantagementioning
confidence: 99%